Criaturas tenebrosas - Stine R. L.; Hernandez, Gabriel; Morse, Scott; Ruth, Greg. (New York, NY : Scholastic, 2007)
Three stories about a werewolf, living scarecrow and the abominable snowman. Based on novels by R.L. Stine.
El hombre lobo del pantano de la fiebre / adapto e ilustrado por Gabriel Hernandez -- El espantapajaros camina a medianoche / adapto e ilustrado por Greg Ruth -- El abominable hombre de las nieves en Pasadena / adapto e ilustrado Scott Morse.
R.L. Stine Goosebumps.
Keywords: Supernatural -- Juvenile literature; Horror tales -- Juvenile literature; Graphic novels